CFD Simulation of oxy-fuel combustion using turbulent non-premixed combustion with medium-rank coal from Kalimantan Indonesia - Agus Prasetyo Nuryadi; R.J. Komara; M.P. Helios; I. Wulandari; Chairunnisa Chairunnisa; Fitrianto Fitrianto (Jurnal POLIMESIN, 2023)
Carbon capture technology connected with oxy-fuel combustion has a high potential for reducing CO2 emissions, particularly in coal-fired power plants. However, the distinct characteristics of each coal depend on its origin. This study analyzes coal combustion from Kalimantan using a drop tube furnace and varying the volume of oxygen: Coal (21 vol.% O2), OF25 (coal with 25 vol.% O2), OF30 (coal with 30 vol.% O2), the non-premixed combustion model and a structured grid. Probability Density Function (PDF) models were used for combustion chemistry. The overall combustion temperature distribution and the amounts of O2, H2O, C, and CO2 in combustion products were visualized. The numerical results show that increasing the volume of oxygen leads to an increase in temperature distribution for OF25 and OF30, but the flame is shorter than for Coal. During combustion, the mass fraction of oxygen remains in the furnace and H2O increases. Carbon burns quickly and is depleted, whereas the CO2 content increases along with the volume of oxygen, making the CO2 capture process easier. The results obtained from the numerical analysis can offer valuable insights for enhancing the design of combustion chambers in oxy-fuel boilers for better modeling of pulverized coal especially using Kalimantan coal.